Optional online quizzes: College student use and relationship to achievement - Genevieve Marie Johnson (The Canadian Network for Innovation in Education (CNIE), 2006)
Online practice tests and quizzes are commonly available to higher education students. The extent of student use of such study tools and the relationship of use to achievement, however, have not been fully investigated. One hundred twelve college students were encouraged to use optional online quizzes in preparation for proctored examinations. In-class examinations included multiple choice items that assessed four cognitive domains: factual, application, comprehension, and conceptual. In general, few students made extensive use of the optional online quizzes. Analysis revealed that student use of online quizzes was associated with increased academic achievement, although it was not clear if quiz use caused achievement or achievement caused quiz use. Short-answer and true-false online quiz items were differentially associated with measures of academic achievement, suggesting that cognitive processing differed across item format. Implications for further research are provided.